Synthesis of 5-arylidenerhodanines in L-proline-based deep eutectic solvent - Hesse, Stéphanie (Beilstein Journal of Organic Chemistry, 2023)
Rhodanines and their derivatives are known to have many pharmacological activities that can be modulated through different functionalization sites. One of the most studied modification in those scaffolds is the introduction of a benzylidene moiety on C5 via a Knoevenagel reaction. Here, a facile synthesis of 5-arylidenerhodanines via a Knoevenagel reaction in an ʟ-proline-based deep eutectic solvent (DES) is reported. This method is fast (1 h at 60 °C), easy, catalyst-free and sustainable as no classical organic solvents were used. The expected compounds are recovered by a simple filtration after hydrolysis and no purification is required. Those derivatives were studied for their antioxidant activities and the results are consistent with those reported in the literature indicating that phenolic compounds are the more active ones.
Keywords: antioxidant; deep eutectic solvent; Knoevenagel; ʟ-proline DES; rhodanine